2013
DOI: 10.12692/ijb/3.10.139-152
|View full text |Cite
|
Sign up to set email alerts
|

Groundwater fauna can be used as indicators of anthropogenic impacts on aquifers: A case study from Meknes area, Morocco

Abstract: The groundwater in the plain of Fez-Meknes constitutes a major resource in the region. The study highlights the importance of this resource, especially its irreplaceability. However, a number of inferences of point source pollution or diffuse were made. In this context, this study aimed at showing the possible relationships between the water quality of wells and springs and the diversity of the aquatic fauna which occurs in these habitats. To this end, the water quality and the fauna were regularly investigate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…More detailed evaluation of the reviewed studies revealed that 70% of studies in Africa concentrated on the description of newly discovered groundwater fauna (Figure 7a). Nevertheless, more than a dozen of studies in Algeria and Morocco conducted eco‐toxicological investigations, revealing that faunal richness in some urban and mining areas is linked with groundwater quality and stygofauna abundance decreases with pollution (Aidaoui, 2019; Boughrous, 2007; Boughrous et al, 2007; Boulaassafer et al, 2021; Boulal et al, 2017; Boutin et al, 1995; Boutin & Idbennacer, 1989; El Adnani et al, 2006, 2007; el Moustaine et al, 2013, 2014; Hallam et al, 2008; Hichem et al, 2019; Laid & Zouheir, 2018; Merzoug et al, 2011, 2014; Ramzi et al, 2020) with authors proposing the use of stygofauna as bioindicators of water quality (Merzoug et al, 2011, 2014). Boulaassafer et al (2021) study on evolutionary processes considerably expanded the knowledge of diversity and geographic range of a freshwater snail genus, and information on endemism and biogeographical distribution of stygobiotic crustacean species of Africa and Madagascar has been recorded (Tuekam Kayo et al, 2012).…”
Section: Global Groundwater Fauna Researchmentioning
confidence: 99%
“…More detailed evaluation of the reviewed studies revealed that 70% of studies in Africa concentrated on the description of newly discovered groundwater fauna (Figure 7a). Nevertheless, more than a dozen of studies in Algeria and Morocco conducted eco‐toxicological investigations, revealing that faunal richness in some urban and mining areas is linked with groundwater quality and stygofauna abundance decreases with pollution (Aidaoui, 2019; Boughrous, 2007; Boughrous et al, 2007; Boulaassafer et al, 2021; Boulal et al, 2017; Boutin et al, 1995; Boutin & Idbennacer, 1989; El Adnani et al, 2006, 2007; el Moustaine et al, 2013, 2014; Hallam et al, 2008; Hichem et al, 2019; Laid & Zouheir, 2018; Merzoug et al, 2011, 2014; Ramzi et al, 2020) with authors proposing the use of stygofauna as bioindicators of water quality (Merzoug et al, 2011, 2014). Boulaassafer et al (2021) study on evolutionary processes considerably expanded the knowledge of diversity and geographic range of a freshwater snail genus, and information on endemism and biogeographical distribution of stygobiotic crustacean species of Africa and Madagascar has been recorded (Tuekam Kayo et al, 2012).…”
Section: Global Groundwater Fauna Researchmentioning
confidence: 99%